TEKNOLOGI PENGOLAHAN TEPUNG MOCAF DENGAN 3 METODE FERMENTASI KAJIAN ANALISA PROKSIMAT - Helilusiatiningsih, Nunuk (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2023)
Mocaf (Modified Cassava Flour) was a product derived from fermented cassava flour. Mocaf has characteristics similar to wheat flour and can be used for processed products such as wet cakes, kue kering, sweet bread, instant noodles and substitutes for certain products, vermicelli, brownies. The problem that occurs was that the price of flour continues to increase along with the high demand, so the price is expensive. The aim of the study was to analyze the nutritional value content, namely proximate in mocaf flour which was processed using 3 fermentation methods. The experimental design is a quantitative analysis method. The parameters measured were water content, ash content, protein, fat, starch. Experimental treatment: there are 3 types of cassava chips processing fermentation methods, namely a. Yeast b. Lime Water c. Enzimo. The results of proximate analysis using the yeast fermentation method contained 13.71% water content, 4.12% ash content, 1.43% crude protein, 2.82% fat, 71.38% starch; Using lime water has a water content of 13.14%, ash 4.82%, protein 1.12%, hasar fat 4.38, starch 69.54%. while the third with enzyme has a water content of 12.66%, ash 3.17, protein 1.83%, fat 3.83%, starch 73%. The ingredient of mocaf flour which has the highest starch was the fermentation method using yeast, the best protein ses the fermentation method with enzymes. The highest fat was mocaf with the fermentation method with lime solution. The water content of flour between the lowest 12 and the highest 13, 66%.